Kinerja PT Wotraco Bali Raya (Ditinjau dari Balanced Scorecard) - FRESSATRIA FRESSATRIA; MADE ANTARA; PUTU UDAYANI WIJAYANTI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2012)
ABSTRACT Performance PT Wotraco Bali Raya (In terms of Balanced Scorecard) Balanced scorecard is a management system for companies to invest in the long termin order to achieve certain financial results that enable the development of a business organization rather than simply managing the bottom line to boost short-termresults. The purpose of this study was to determine the performance of PT Wotraco Bali Raya viewed from four perspectives of balanced scorecard namely financial perspective, customer perspective, internal business process perspective, and learning and growth perspective of the year 2009 till 2011.The research was conducted in PT Wotraco Bali Raya which is housed in the 116 Tukad Pakerisan Denpasar. Types of data collected in clude quantitative and qualitative data. Data collection methods used were interviews, observation, and study documentation. The results showed the performance of PT Wotraco Bali Raya from 2009 till 2011 from a financial perspective gained an average of 169.87% current ratio, debt to total assets ratio of 203.14%, and the net profit margin of 22.12%. From the perspective of the customer, the customer growth rate obtained for 2.43%, and the rate of repeat customers and customer satisfaction is not still providea positive perception or satisfied. From the perspective of internal business process efficiency product order transaction completion time obtained an average of 1.29 MCE. From the perspective of learning and growth, the level of productivity of employeesearned an averageof Rp. 1,088,821.18, the retention rate of employeesearnan average of 3.33%, and the level of employee satisfaction providesa positive perception or satisfied. Based on this research,the authors suggestion is the need for companies rais edfunds, to maintain quality of service to customers, and maintaining the reservation service. Keyword: Perfomance, Companies, Balanced Scorecard